2013
DOI: 10.1007/s13149-013-0299-4
|View full text |Cite
|
Sign up to set email alerts
|

Données épidémiologiques, cliniques et thérapeutiques des patients infectés par le VIH sous traitement antirétroviral à l’hôpital de Ségou au Mali (2004–2011)

Abstract: This is a retrospective study on a cohort of 811 adult patients placed on ART between January 2004 and December 2011 at the hospital Nianankoro Fomba Segou in Mali, to describe their epidemiological, clinical and developmental profile for 48 months. The average age of patients was 35.2±9.4 years. The sex-ratio was 0.6. Approximately 58.3% of the patients were from rural areas. HIV1 represented 95.8%. Prolonged fever, weight loss and chronic diarrhea were the main reasons for testing. The majority of patients (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 3 publications
0
4
0
6
Order By: Relevance
“…These outcomes are superimposable to the ones of Marazzi [9] who reported 34% as prevalence of undernutrition in HIV infected patients. Koné [10] reported a body mass index average of 17.2 ± 3.06 kg/m 2 , indicator of undernutrition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These outcomes are superimposable to the ones of Marazzi [9] who reported 34% as prevalence of undernutrition in HIV infected patients. Koné [10] reported a body mass index average of 17.2 ± 3.06 kg/m 2 , indicator of undernutrition.…”
Section: Discussionmentioning
confidence: 99%
“…Déguénonvo [4] reported that 88% of his range patients were at stage IV of WHO. Koné [10] reported that 64.50% of the patients were at stage III and 15.70% at stage IV. Dicko [11] reported similar results with 64% at stage IV and 27% at the stage III.…”
Section: Cd4 Cells Levelmentioning
confidence: 99%
“…L'âge moyen de patients dans le travail de Déguénonvo et al [16] était de 41±10 ans ; il était de 30 à 44 ans dans 59 % pour Kautako et al [17], de 35 à 44 ans chez Kakisingi et al [19], de 42± 9,3 ans pour Tshingani et al [20]. Pour Kone et al [26] [27], le sex ratio H/F était de 0,9 et Mbopi et al [6] n'avait que 45,6 % de femmes. La femme présente une vulnérabilité biologique, sociale (pauvreté et polygamie) et économique [28][29].…”
Section: Infections Opportunistes Et Autres Comorbiditésunclassified
“…Cette répartition est conforme à la configuration de la répartition de croyants des Eglises en RDC. Kautako et al [17], Tshingani et al [20], Koné et al [26] et Zannou et al [27] ne font pas allusion à la religion dans leurs séries respectives. La religion peut avoir un impact positif ou négatif sur la prise en charge (PEC) de l'infection à VIH.…”
Section: Infections Opportunistes Et Autres Comorbiditésunclassified
“…The current socio-demographic profile of people newly infected with HIV in Northern Benin is largely comparable to that described in most of the studies conducted in sub-Saharan Africa. AIDS remains in Benin and sub-Saharan Africa a disease affecting mostly young people, predominantly female, resident in urban areas and having low purchasing power [9][10][11][12]. It emerges from this study that preventive measures should be given priority to young girls in urban areas, with low incomes and in liberal professions such as hairdressing, sewing, resale or small business.…”
Section: Socio-demographic Profile Of Patients Newly Diagnosed Hiv-pomentioning
confidence: 99%